Management of firearm facial fractures at the ‘‘Dr. José Eleuterio González’’: University Hospital Case Report - González Vargas, Iram Zeyn; García Pérez, Mauricio; Castro Govea, Yanko; Franco Vasquez, Christian Eduardo; Juárez López de Nava, Abraham; Fonseca Sada, José Ignacio (UANL. Facultad de Medicina, 2016)
Gunshot wounds in the facial region produce important functional disabilities if they are not properly treated. They may also cause an important effect in the social and psychological development of the patient because of the aesthetic problems that they produce. This article presents a case of a 20 years-old female patient who was referred to our institution because of facial trauma secondary to a gunshot wound, whose treatment consisted of multiple reconstructive surgeries in order to obtain an adequate, functional and esthetic result. Also, we did a review of the bibliography in order to establish the proper management of the wounds found in these type of cases.